The Structure of Character in the Novel "Arsh Mu‘ashaq" by: Rabia Jallati - Bouchlalek , Abdelaziz; Al-Aifa, Nour El-Huda (El Omda in Linguistics and Discourse Analysis, 2020)
Abstract: The novel is first of all a formation based on the imagination of the novelist, a very large project that combines the history and criticism of the society, when the piece devoted to its novelist incarnation added attention to the society and the character of the heroine, thus allowing the personality to multiply through a relational network of analogies, hierarchies and collective regularities because what is associated with the personality of social and linguistic relations and behaviour, and of this work, was working in this article on the novel "the throne " of: Rabia Jallati as a model for the study..